2021
DOI: 10.1039/d1tc00440a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering donor–acceptor conjugated polymers for high-performance and fast-response organic electrochemical transistors

Abstract: To date, high-performance organic electrochemical transistors (OECTs) are mostly based on polythiophene systems. Donor-acceptor (D-A) conjugated polymers are expected to be promising materials for OECTs owing to their high mobility...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 47 publications
2
79
0
Order By: Relevance
“…47 Contrary to what we mentioned above, Giovannitti and co-workers emphasized that polymers with large IPs can shift the operational voltages of OECTs to avoid oxygen reduction reaction (ORR) occurring in ambient conditions. They demonstrated that p(gPyDPP-2MeOT) (IP = 5.0 eV) did not undergo ORR in ambient 36 and Lei et al 39 DPP-based high-performance OECTs separately almost at the same time (Figure 6E). Although the backbone structure is the same, they get different results and conclusions.…”
Section: The Third-generation Semiconducting Polymers For Oectsmentioning
confidence: 94%
See 2 more Smart Citations
“…47 Contrary to what we mentioned above, Giovannitti and co-workers emphasized that polymers with large IPs can shift the operational voltages of OECTs to avoid oxygen reduction reaction (ORR) occurring in ambient conditions. They demonstrated that p(gPyDPP-2MeOT) (IP = 5.0 eV) did not undergo ORR in ambient 36 and Lei et al 39 DPP-based high-performance OECTs separately almost at the same time (Figure 6E). Although the backbone structure is the same, they get different results and conclusions.…”
Section: The Third-generation Semiconducting Polymers For Oectsmentioning
confidence: 94%
“…However, the molecular weight of D-A polymers is limited when grafted with EG side chain. 37,38 Recently, Lei et al optimized the catalyst and solvent in Stille polymerization 39 and found that Pd(PPh 3 ) 4 /Pd(PPh 3 ) 2 Cl 2 and N,N-dimethylformamide/chlorobenzene 1:1 mixture can provide significantly higher molecular weights, which can solve the low-molecular weight issue for ethylene glycol (EG) side chain polymers.…”
Section: Materials Type and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…McCulloch et al have recently reported three donor-acceptor (D-A) type glycolated TDPPs and highlighted the relationship between the polaron delocalization and the OECT mobility. One of these DPP polymers had a high mC* of about 300 F cm À1 V À1 s À1 but a high threshold voltage of 0.52 V. [37][38][39][40][41] Thienylenevinylene (TVT) and thiophene-benzothiadiazole-thiophene (TBTT) are two popular electron-donating units used to form D-A type polymers with high charge-carrier mobilities in OFETs. [42][43][44] Incorporating the highly p-extended TVT and TBTT units in the main chain with DPP promotes intermolecular p-p stacking.…”
Section: Introductionmentioning
confidence: 99%
“…H and19 F NMR, as well as MALDI-ToF analysis (FiguresS23-S28).Solution state UV/Vis spectra in CHCl 3 (FiguresS29-32) of PgBT(F)2gT and PgBT-(F)2gTT revealed evidence of aggregation. Both polymers exhibited a main absorption around 600 nm with a longer wavelength shoulder which dissipated at increased temperatures.…”
mentioning
confidence: 99%